Brandon/Hill selected list of books and journals in allied health. - Hill, D R (1998)
This list of 410 books and 78 journals is intended as a selection guide to be used in a library supporting allied health educational programs or allied health personnel in either an academic or health care setting. Because of the impossibility of covering the large number and wide variety of allied health professions and occupations, the recommended publications are focused primarily on the educational programs listed and described in the AMA's Health Professions Education Directory, 1997-1998, plus physical therapist and medical secretary. Some programs do not have their own specific literatures. Books and journals are categorized by subject; the book list is followed by an author/editor index, and the subject list of journals by an alphabetical title listing. Items suggested for initial purchase (160 books and 31 journals) are indicated by asterisks. To purchase the entire collection of books and journals (1998 subscriptions) would require an expenditure of about $29,180. The cost of only the asterisked items total $11,390.